Short Terms Safety of Chinese Origin Covid-19 Vaccine in Cardiac Patients - Muhammad Abdur Rauf, Yasir Arafat, Iqtidar-Ud-Din, Syed Tahir Shah, Sumia, Sajjad Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out short terms safety of Chinese origin Covid-19 vaccines in cardiac patients. To identify frequency of major and minor cardiovascular events in Covid-19 vaccinated cardiac patients. Methodology: It was a cross sectional study conducted in Qazi Hussain Ahmad Medical Complex Nowshera and Kuwait Teaching Hospital Peshawar, Pakistan from February 2021 to April 2021 on a sample of 325 cardiac patients irrespective of their gender. Cardiac patients who received 2 doses of sinopharm vaccine were included in our study. The clinical characteristics of patients included age, gender, comorbids like diabetes and hypertension and those patient s who have undergone any cardiac procedures i-e post CABG and post PCI. The data was analyzed with SPSS version Results: Total 325 known cardiac patients who received 2 doses of sinopharm vaccine were enrolled in the study, among them 198 were male and 127 were female. Participants age range was 56.48±5.9 years and among them mean age of male was 56.59±6.55 years and of female was 57.64±4.27 years. Among the participants 76(23.3%) were hypertensive out of which 44(22.2%) were male. Total number of diabetics were 98(30.15%) among which 59(29.79%) were male. Post CABG patients were 56(17.23%) in number, and among these 34(17.17%) were male. Among them 176(54.15%) were post PCI and among these 102(51.51%) were male. Out of total 325 participants the frequency of major adverse cardiovascular events was 4(1.2%) which include major cardiovascular events , death of any cause, urgent repeat revascularization, MI (not revascularized) an ischemic stroke were 1.2%, 0.91%, 0.31%, 0.92%, 0% respectively. Frequency of minor adverse cardiovascular events in cardiac patients after sinopharm vaccination was 4(1.2%) out of total 325 participants. which include minor cardiovascular events(9.85%), atrial fibrillations(0.92%), complete heart block(0%), increase in angina functional class(2.46%), increase in NYHA functional class(2.53%), and palpitations(3.69%). Conclusion: Chinese origin covid-19 vaccine (sinophorm) is safe in cardiac patients and has minor side effects and rare major side effects in cardiac patients. Keywords: Sinopharm vaccine, Cardiac patients, Corona virus